2007
DOI: 10.1016/j.jcrs.2006.10.066
|View full text |Cite
|
Sign up to set email alerts
|

Contrast sensitivity after implantation of a spherical versus an aspherical intraocular lens in biaxial microincision cataract surgery

Abstract: No clinically relevant postoperative differences in contrast sensitivity were observed between the aspherical microincision IOL and the spherical equivalent model. The development of microincision IOLs, which fit through corneal incisions smaller than 2.0 mm and improve night-driving conditions (eg, reduction of glare), could optimize modern biaxial cataract surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
49
1

Year Published

2007
2007
2012
2012

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(51 citation statements)
references
References 26 publications
1
49
1
Order By: Relevance
“…6 Both in the laboratory by using adaptive optics 3 and in clinical studies, aspheric IOLs have been shown to reduce ocular SAs, improve contrast sensitivity, and improve night driving performance. 2,4 However, 2 recent studies 13,14 reported no differences between aspheric and spherical IOLs in low-contrast visual acuity, high-contrast visual acuity, and contrast sensitivity. Although multiple factors may contribute to these conflicting findings, lack of optimization of residual ocular SA might play a role.…”
Section: Discussionmentioning
confidence: 99%
“…6 Both in the laboratory by using adaptive optics 3 and in clinical studies, aspheric IOLs have been shown to reduce ocular SAs, improve contrast sensitivity, and improve night driving performance. 2,4 However, 2 recent studies 13,14 reported no differences between aspheric and spherical IOLs in low-contrast visual acuity, high-contrast visual acuity, and contrast sensitivity. Although multiple factors may contribute to these conflicting findings, lack of optimization of residual ocular SA might play a role.…”
Section: Discussionmentioning
confidence: 99%
“…6,7 Spherical intraocular lenses (IOLs) have positive spherical aberration that increases the total ocular spherical aberration in conjunction with that of the cornea and in turn degrades visual quality. 8 Patients with standard spherical IOLs were found to have reduced contrast sensitivity compared with that in the normal phakic population. 9 Aspheric IOLs were designed to reduce the positive spherical aberration of the cornea, improving contrast sensitivity under nonphotopic conditions over that with standard spherical IOLs.…”
mentioning
confidence: 98%
“…Three aspheric IOL designs are currently marketed: Tecnis Z9000/2/3 (AMO), Acrysof IQ and Adapt AO. Tecnis Z9003 and Acrysof IQ produce negative spherical aberration (-0.27 and -0.20 m, respectively, measured at the 6-mm optic zone) to offset the positive spherical aberration of the average cornea [21] .…”
Section: Discussionmentioning
confidence: 99%